Does hepcidin take role on anemia in rheumatoid arthritis? - Isik, A.; Koca, S.; Metin, K.; Ustundag, B.; Dag, S. (B M J Publishing Group, 2007)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR 2007) -- JUN 13-16, 2007 -- Barcelona, SPAIN